2011
DOI: 10.5755/j01.sal.0.19.945
|View full text |Cite
|
Sign up to set email alerts
|

Video Game Localization: the Analysis of In-Game Texts

Abstract: Globalisation acts as a driving force to present a variety of commercial products, including games, in different languages simultaneously so that they could reach auditoria and be enjoyed around the globe at the same time. Being the member of the European Union, Lithuania is not an exception in the process of globalisation. With the help of localisation various types of documents, software and products are adapted to the Lithuanian culture and market. However, the industry of game localisation of high or at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Looking more closely at research on text material being vocalized in participants' reading-aloud actions in game activity contexts, studies show that these so-called ingame texts [3] provide valuable resources for the players' joint goal orientation within the game activity [9]. It can also be found that the way they are located, formulated [10] (and translated [11]) influences the degree of supportiveness for the activity and the way the participants turn towards these written informings and similar activity-relevant information [12].…”
Section: Interface Designmentioning
confidence: 99%
See 3 more Smart Citations
“…Looking more closely at research on text material being vocalized in participants' reading-aloud actions in game activity contexts, studies show that these so-called ingame texts [3] provide valuable resources for the players' joint goal orientation within the game activity [9]. It can also be found that the way they are located, formulated [10] (and translated [11]) influences the degree of supportiveness for the activity and the way the participants turn towards these written informings and similar activity-relevant information [12].…”
Section: Interface Designmentioning
confidence: 99%
“…Thereafter Ted expands his previous read-aloud turn (l. 7) with a stressed and stretched pivotal marker ('so', l. 9) [see e.g., 24 or 25]. When no one jumps in offering relevant information, Liv makes an account for her understanding of the way (at least) the steering is handled ('it's me who could control it', l. [11][12]. She does that with intonation rising high at the ends of both sentences, prosodically realizing a question for clarification.…”
Section: Vtcpuetkrv"3mentioning
confidence: 99%
See 2 more Smart Citations
“…As in Mateusz (2014), video game translation is interwoven with the source code of a particular product. As presented in Šiaučiūnė andLiubinienė (2011), Chroust (2007) elaborates localization as multi-layered process in the form of pyramid performed at different levels:…”
Section: Video Game Localizationmentioning
confidence: 99%